La necesidad de regular en el código de trabajo ecuatoriano, la modalidad de trabajo autónomo, en relación al artículo 329 de la Constitución de la República del Ecuador La necesidad de regular en el código de trabajo ecuatoriano, la modalidad de trabajo autónomo, en relación al artículo 329 de la Constitución de la República del Ecuador - Merino Cabezas, Esteban Francisco (2015)
Our Constitution of the Republic of Ecuador, recognizes and guarantees the right to work for all citizens of this country. As progress in labor and rights, the current Constitution guarantees a new way of working which incidentally has been doing since long ago, such as self-employment or self, ie this type of work the number of people currently engaged and is fully guaranteed in our Constitution. Before the validity of the constitutional provision guaranteeing self-employment or self, is delivering a series of problems of a legal and social with people who engage in this activity specifically with street vendors, who are coming affecting various rights of a personal nature and their assets, a situation that despite being already recognized in our Constitution's still seeing all this on the grounds that to this date still has not been in one way or another reflect this constitutional guarantee in our labor code as a way of working, which in addition to guaranteeing the right to work to those engaged in this activity, they can facilitate access to social security. Therefore in this paper reflected the theoretical arguments, results of field research and analysis which demonstrates the need for self-employment or self-recognition in the Constitution of the Republic shall see properly regulated in the Code working as a way of working, being this the main point of my thesis work, which I hope will help solve this problem.